Rare Copy Number Variants Intersecting Parkinson’s-associated Genes in a Cohort of children With Autism Spectrum Disorders - Alina Erbescu; Sorina Mihaela Papuc; Magdalena Budișteanu; Maria Dobre; Catrinel Iliescu; Mihail Eugen Hinescu; Aurora Arghir; Monica Neagu (Neuroscience Insights)
Autism spectrum disorders (ASDs) are neurodevelopmental conditions characterized by important clinical and genetic heterogeneity. Recent studies suggested an overlap between ASD and Parkinson's disease (PD) in terms of clinical manifestation and underlying genetic defects. Our aim was to assess using a chromosomal microarray assay the frequency of rare exonic deletions that overlap with PD associated genes in a pediatric ASD group. Three hundred and five children diagnosed with ASD were enrolled in a study focused on deep phenotyping and genomic profiling by chromosomal microarrays. In the investigated group, four children with ASD harbored deletions encompassing genes involved in Mendelian forms of PD or contributing to PD risk. Deletions of Parkin RBR E3 ubiquitin protein ligase ( PRKN) and synuclein alpha interacting protein ( SNCAIP ) were found in one patient, each; two other patients showed intragenic deletions of Rab9 effector protein with kelch motifs ( RABEPK ). Our study found that deletions involving genes associated with PD are rare events, as we identified approximately 1% in the ASD cohort of children. Our data adds to the previous reports of rare genomic imbalances of PD associated genes in ASD, further supporting the hypothesis that these conditions might share molecular mechanisms of pathogenesis.